From Waste to Value: The Economic Impact of Circular Economy Practices on SDG Achievement in Spain’s Tire Industry (European Journal of Marketing and Economics, 2024)
This study explores the intersection of circular economy practices and sustainable development within the framework of stakeholder theory, emphasizing the strategic importance of waste valorization for achieving long-term socio-economic objectives. Focusing on the case of used tires in Spain, the research evaluates how public and private sector actors contribute to the implementation of circular economy policies and their alignment with the United Nations Sustainable Development Goals (SDGs). Drawing on recent developments in industrial ecology and sustainable waste management, the paper analyzes the value generated through tire recycling initiatives, considering both environmental outcomes and economic returns. The role of stakeholder collaboration—across government bodies, manufacturers, and recycling firms—is critically examined to assess how these efforts collectively impact specific SDGs. Findings indicate significant progress in areas such as responsible consumption, climate action, and innovation, while also identifying gaps in regulatory coordination and infrastructure. This case demonstrates how the circular economy can serve as a catalyst for sustainable industrial transformation and provides insights for policymakers and industry leaders aiming to integrate sustainability into economic planning.
Keywords: Circular Economy, Sustainable Development Goals (SDGs), Waste Management, Tire Recycling, Stakeholder Engagement, Spain, Industrial Ecology